Fiscal Policy and Economic Growth in Iraq: An ARDL Analysis of an Oil-Dependent Economy (2004 2024) - Thaer Mohammed Nsaif; Akram Salih Yousif; Mamon Adam Maarof (AL-ARBAH: Journal of Islamic Finance and Banking, 2026)
Purpose - This study explores how fiscal policy influences economic growth in Iraq during the period 2004–2024, with a particular focus on the challenges faced by oil-dependent economies. Method - To achieve this objective, the study applies the ARDL model to examine both short-term adjustments and long-term relationships using annual time-series data. The analysis includes key macroeconomic variables such as GDP, government expenditure, oil revenues, tax revenues, money supply, and exchange rate. The Phillips–Perron test is used to ensure data stationarity. Result - The results indicate that economic growth in Iraq is closely tied to fluctuations in oil revenues, which largely drive fiscal activity. Government spending follows oil income patterns but shows limited independent impact in the long run. In contrast, non-oil fiscal tools, particularly taxation, play a relatively weak role, reflecting the narrow fiscal base of the economy. Implication - These findings suggest that improving fiscal policy effectiveness requires reducing reliance on oil revenues, strengthening the tax system, and enhancing the efficiency of public spending. Originality - This study presents a comprehensive assessment by combining numerous financial variables within a unified economic model, giving a clearer understanding of how fiscal policy works in a resource-based economy like Iraq. Keywords: Fiscal policy, Economic growth, Oil-dependent economy, ARDL, Iraq